Unprecedented in vivo activity of telacebec against Mycobacterium leprae - Chauffour, Aurélie; Cambau, Emmanuelle; Pethe, Kevin; Veziris, Nicolas; Aubry, Alexandra (PLOS Neglected Tropical Diseases, 2025)
Background New drugs targeting the electron transport chain (ETC) seem to be a promising advance in leprosy treatment. In this study, we evaluated the bactericidal activity of telacebec (TCB), a phase 2 drug candidate for tuberculosis, alongside known ETC-targeting antibiotics, bedaquiline (BDQ) and clofazimine (CFZ), as monotherapy or in combination. Methodology/ Principal Findings We used the reference leprosy proportional bactericidal mouse footpad model. Four hundred and ten mice were inoculated in the footpads with 5x104 to 5x100 bacilli of M. leprae strain THAI53 for the untreated control group and groups treated with drug-monotherapies, and with 5x104 to 5x101 for groups treated with drug-combinations. Mice were randomly allocated into the following groups: 2 control groups (untreated or standard multi drug therapy (MDT), rifampin, dapsone and clofazimine with dosing equipotent to human dosing) and 7 test groups (TCB 10mg/kg, bedaquiline 25mg/kg (BDQ), clofazimine 20mg/kg (CFZ), CFZ + BDQ, TCB + BDQ, TCB + CFZ, TCB + CFZ + BDQ). Mice in the test groups received either one month treatment (MDT) or a single dose of the drugs (TCB, RIF, BDQ, CFZ). Twelve months later, mice were sacrificed to enumerate M. leprae bacilli in the footpad. All the footpads became negative in the MDT, TCB and combination groups except in the TCB + CFZ group where 2 mice remained positive in the 5x104 inoculum. Conclusion We demonstrated that monotherapy of TCB exhibited bactericidal activity against M. leprae comparable to that of MDT and that all combination therapies were as effective as MDT, except the combination TCB + CFZ, possibly due to an antagonism between these two drugs.